Quality of traditional salt in the Tiberias Group, West Oesapa Village, Kelapa Lima District, Kupang City.: Quality of traditional salt in the Tiberias Group, West Oesapa Village, Kelapa Lima District, Kupang City. - Umbu Paru Lowu Dawa; Mada Maria Lakapu; Dewi Setyowati Gadi; Yunialdi H. Teffu; Donny M. Bessie; Santo P.A. Naliama; Yanuarinda Seuk Seran; Dewanto Umbu S. Anakaka (IJOTA (Indonesian Journal of Tropical Aquatic), 2022)
The purpose of this study was to analyze the quality of traditional salt through organoleptic tests (color and aroma), water content, NaCl content and total plate number (TPN). This research uses quality and quantity methods, data analysis method is a comparative descriptive method. The results showed that the quality of the salt produced traditionally through organopleptic tests had a color and aroma were acceptable NSI 4435-2017, the water control has met NSI 3556-2016 and NSI 4435-2017, while the NaCl content did not meet NSI 3556-2016, but it complied with NSI. 4435-2017 and the Total Plate Number (TPN) in coarse salt 2.7 × 102– 3.6 × 102 colony/g, well water 1.3 × 103– 1.8 × 103colonies/ml, filtering solution 1.9 × 103– 2.3 × 103 colonies/ml, filtered solution 1.6 × 103– 1.8 × 103colonies/ml. Meanwhile, the cooked salt was < 2.5 × 101colony/g (<25 colonies).